babyagelesszj

Answered

2022-07-01

If $A+B+C=\frac{\pi}{2}$ thrn prove that:

$\mathrm{tan}(A+B)[\mathrm{tan}A-\mathrm{tan}B]=\sqrt{1+{\mathrm{cot}}^{2}C}(\mathrm{sec}A\mathrm{cos}B-\mathrm{cos}A\mathrm{sec}B)$

$\mathrm{tan}(A+B)[\mathrm{tan}A-\mathrm{tan}B]=\sqrt{1+{\mathrm{cot}}^{2}C}(\mathrm{sec}A\mathrm{cos}B-\mathrm{cos}A\mathrm{sec}B)$

Answer & Explanation

Janiyah Patton

Expert

2022-07-02Added 12 answers

Here,

$A+B+C=\frac{\pi}{2}$

$A+B=\frac{\pi}{2}-C$

Now,

$L.H.S.=\mathrm{tan}(A+B)[\mathrm{tan}A-\mathrm{tan}B]=\mathrm{tan}(\frac{\pi}{2}-C)(\frac{\mathrm{sin}A}{\mathrm{cos}A}-\frac{\mathrm{sin}B}{\mathrm{cos}B})$

$\begin{array}{rl}\mathrm{cot}C\frac{\mathrm{sin}(A-B)}{\mathrm{cos}A\mathrm{cos}B}& =\frac{\mathrm{cos}C}{\mathrm{sin}C}\frac{\mathrm{sin}(A-B)}{\mathrm{cos}A\mathrm{cos}B}\\ & =\frac{\mathrm{sin}(A+B)}{\mathrm{cos}(A+B)}\frac{\mathrm{sin}(A-B)}{\mathrm{cos}A\mathrm{cos}B}\\ & =\frac{\frac{\mathrm{cos}2B-\mathrm{cos}2A}{2}}{\mathrm{sin}C(\mathrm{cos}A\mathrm{cos}B)}\\ & =\frac{{\mathrm{cos}}^{2}B-{\mathrm{cos}}^{2}A}{\mathrm{sin}C\mathrm{cos}A\mathrm{cos}B}\\ & =\frac{1}{\mathrm{sin}C}(\mathrm{sec}A\mathrm{cos}B-\mathrm{cos}A\mathrm{sec}B)\\ & =\text{cosec}C(\mathrm{sec}A\mathrm{cos}B-\mathrm{cos}A\mathrm{sec}B)\\ & =\sqrt{1+{\mathrm{cot}}^{2}C}(\mathrm{sec}A\mathrm{cos}B-\mathrm{cos}A\mathrm{sec}B)\end{array}$

$A+B+C=\frac{\pi}{2}$

$A+B=\frac{\pi}{2}-C$

Now,

$L.H.S.=\mathrm{tan}(A+B)[\mathrm{tan}A-\mathrm{tan}B]=\mathrm{tan}(\frac{\pi}{2}-C)(\frac{\mathrm{sin}A}{\mathrm{cos}A}-\frac{\mathrm{sin}B}{\mathrm{cos}B})$

$\begin{array}{rl}\mathrm{cot}C\frac{\mathrm{sin}(A-B)}{\mathrm{cos}A\mathrm{cos}B}& =\frac{\mathrm{cos}C}{\mathrm{sin}C}\frac{\mathrm{sin}(A-B)}{\mathrm{cos}A\mathrm{cos}B}\\ & =\frac{\mathrm{sin}(A+B)}{\mathrm{cos}(A+B)}\frac{\mathrm{sin}(A-B)}{\mathrm{cos}A\mathrm{cos}B}\\ & =\frac{\frac{\mathrm{cos}2B-\mathrm{cos}2A}{2}}{\mathrm{sin}C(\mathrm{cos}A\mathrm{cos}B)}\\ & =\frac{{\mathrm{cos}}^{2}B-{\mathrm{cos}}^{2}A}{\mathrm{sin}C\mathrm{cos}A\mathrm{cos}B}\\ & =\frac{1}{\mathrm{sin}C}(\mathrm{sec}A\mathrm{cos}B-\mathrm{cos}A\mathrm{sec}B)\\ & =\text{cosec}C(\mathrm{sec}A\mathrm{cos}B-\mathrm{cos}A\mathrm{sec}B)\\ & =\sqrt{1+{\mathrm{cot}}^{2}C}(\mathrm{sec}A\mathrm{cos}B-\mathrm{cos}A\mathrm{sec}B)\end{array}$

Most Popular Questions